New Neolithic evidence from the al-Jawf region: an outline of the historical development of Dūmat al-Jandal - Loreto, Romolo (Proceedings of the Seminar for Arabian Studies, 2013)
This paper presents the preliminary results of a survey undertaken during the third Saudi-Italian-French archaeological campaign at Dümat al-Jandal, ancient Adummatu, between October and November 2011. The field survey incorporated a range of scientific approaches to the study of the ancient site and the morphological development of the al-Jawf area. A particular focus of the season was the preliminary geomorphological survey of the Wâdï al-Sirhän region, in order to study the palaeo-environmental development of Dümat al-JandaFs surroundings.